Herpes simplex virus encephalitis in an 8 years old with normal cerebrospinal fluid and negative herpes simplex virus polymerase chain reaction - A clinical and radiological diagnosis - Singh, Parminder; Gupta, Divya (Indian Journal of Child Health, 2018)
Herpes simplex encephalitis is known to cause significant morbidity and mortality both in children and adults. Polymerase chain reaction (PCR) for herpes simplex virus (HSV) in cerebrospinal fluid (CSF) is the diagnostic modality accepted worldwide. However, a negative CSF HSV PCR result should always be interpreted in the context of the timing of specimen collection and also considering the clinical picture. We report a case of HSV encephalitis in an 8-year-old male child whose initial CSF picture was normal and CSF for HSV PCR was also negative. However, the magnetic resonance imaging brain findings and clinical profile along with a marked response to acyclovir therapy started very early in the course of illness left little doubts about the diagnosis.